(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research investigates the impact of HRM practices in reducing employee dissatisfaction, turnover and on achieving organizational brilliance excellence. The study utilized a quantitative methodology involving a structured questionnaire administered to a total of 243 HR managers, to collect comprehensive data on employee experiences and organizational performance. The primary objectives were to assess the role of HRM practices in reducing employee dissatisfaction and its effect on organizational performance. The findings reveal that decreased employee dissatisfaction and turnover significantly enhances organizational performance, stability, and competitiveness, while lower levels of employee dissatisfaction lead to improved employee engagement, teamwork, and client relations. Statistical analysis, including one-sample tests, confirmed that the observed effects were both substantial and statistically significant, indicating that addressing these factors can lead to meaningful improvements in organizational outcomes. The results underscore the importance of strategic initiatives focused on minimizing turnover and dissatisfaction to foster a productive and positive work environment, ultimately contributing to organizational excellence. This study provides valuable insights for human resource practitioners and organizational leaders, highlighting effective strategies for managing employee-related challenges.